Computational Fluid Dynamics of Reacting Flows at Surfaces: Methodologies and Applications. Issue 5 (26th February 2022) - Micale, Daniele; Ferroni, Claudio; Uglietti, Riccardo; Bracconi, Mauro; Maestri, Matteo
Abstract: This review presents the numerical algorithms and speed‐up strategies developed to couple continuum macroscopic simulations and detailed microkinetic models in the context of multiscale approaches to chemical reactions engineering. CFD simulations and hierarchical approaches are discussed both for fixed and fluidized systems. The foundations of the methodologies are reviewed together with specific examples to show the applicability of the methods. These concepts play a pivotal role to enable the first‐principles multiscale approach to systems of technological relevance. Abstract : The numerical methodologies and speed‐up strategies to couple computational fluid dynamics and first‐principles chemical kinetics are reviewed in the context of fixed and fluidized catalytic units. These concepts play a pivotal role to enable the multiscale analysis of reactive systems of technological relevance.